2020
DOI: 10.1155/2020/1589150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physicochemical and Cooking Characteristics of Rice (Oryza sativa L.) Landraces of Lamjung and Tanahun Districts, Nepal

Abstract: After the Green Revolution, the increase in the choice of modern varieties at the expense of landraces has become a major cause of varietal loss. The preference, choice, and the economy of rice (Oryza sativa L.) largely depend on its physicochemical and cooking properties, which are found to be superior for landraces than modern varieties. In this study, we assessed and evaluated milled rice of 30 rice landraces on their physicochemical and cooking characteristics which aim to promote the revival of old landra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 24 publications
8
34
5
Order By: Relevance
“…The majority of the landraces in this study registered soft gel consistency, this could be due to the low level of amylose content since these traits were related to each other (Jan and Subhash, 2020). Rice with soft gel consistency cooks more tenderly and remains soft even after cooling (Pokharel et al, 2020). Similar results of soft GC in most of the genotypes were reported by Bharath et al (2018) and found that rice remains soft after cooking was due to soft GC.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The majority of the landraces in this study registered soft gel consistency, this could be due to the low level of amylose content since these traits were related to each other (Jan and Subhash, 2020). Rice with soft gel consistency cooks more tenderly and remains soft even after cooling (Pokharel et al, 2020). Similar results of soft GC in most of the genotypes were reported by Bharath et al (2018) and found that rice remains soft after cooking was due to soft GC.…”
Section: Resultssupporting
confidence: 82%
“…Most consumers prefer rice with intermediate AC since cooked rice will be soft, flaky with good palatability (Cuevas et al, 2018). Amylose content variation in all levels (low, intermediate and high) in rice landraces was reported by Sahu et al (2017), Taratima et al (2019) and Pokharel et al (2020). This could be due to the variation in genetic level.…”
Section: Resultsmentioning
confidence: 97%
“…Similar results were obtained by [22] where the first five principal components were found to be significant and contributed 82.9% of the total variation in 31 rice germplasm. In a study of cooking and physicochemical characters using the same landraces, the first four principal components retained 73.8% of the total variance [23]. e proper value measures the importance and contribution of each component to total variance, whereas each coefficient of the proper vectors indicates the degree of contribution of every original variable with the principal component it is associated with [24].…”
Section: Resultsmentioning
confidence: 99%
“…They also suggested that cultivars with higher ratio of length and width (L:W ratio) show higher degree of milling (DOM). Besides the varietal differences, the type of mill used for milling also highly affects the bran percentage and milling recovery [35][36]. In the present study, the weight of rice bran separated by the polishing method was expressed as DOM.…”
Section: Simple Methods For Estimation Of Dietary Fibre Content In Whole Grain Rice Based On the Bran Fraction Weightmentioning
confidence: 99%